Efficiency, Challenges, and Solution in Online Learning for The Better Standard of Living in Public Schools - Charles Donako (Lentera Ilmu Madani, 2026)
The Covid-19 pandemic presents challenges to education with a different learning system, namely from offline to online based. The current Covid-19 has had a huge impact on education, because many students in public schools are forced to work to help support their families' finances. Data from the ministry of education shows that many students stopped their education during the pandemic because of these obstacles. In fact, students also experience a decrease in their enthusiasm for learning due to the high activity of playing online games and social media. They experience dependence on the internet (internet addiction) which causes a decrease in enthusiasm for learning. However, in this digital era, the current generation cannot resist the changes that are occurring, all aspects of life must be able to unite in creating effective online learning. This research aims to examine the efficiency, challenges and solutions of online learning for a better standard of living in public schools during a pandemic. The results of this study are expected to improve the quality of online learning to be more effective and to increase learning motivation. We use mix method research by collecting data through surveys and interviews. Interview data will be processed with NVivo 12 and for survey analysis processed with SEM-PLS. This research contributes to improving online learning arrangements so that they are more optimal.